Atorvastatin Attenuates Isoflurane-Induced Activation of ROS-p38MAPK/ATF2 Pathway, Neuronal Degeneration, and Cognitive Impairment of the Aged Mice - Liu, Pengfei; Gao, Quansheng; Guan, Lei; Sheng, Weixuan; Hu, Yanting; Gao, Teng; Jiang, Jingwen; Xu, Yongxing; Qiao, Hui; Xue, Xinying; Liu, Sanhong; Li, Tianzuo (Frontiers in Aging Neuroscience, 2021)
Isoflurane, a widely used volatile anesthetic, induces neuronal apoptosis and memory impairments in various animal models. However, the potential mechanisms and effective pharmacologic agents are still not fully understood. The p38MAPK/ATF-2 pathway has been proved to regulate neuronal cell survival and inflammation. Besides, atorvastatin, a 3-hydroxy-3-methyl-glutaryl coenzyme A reductase inhibitor, exerts neuroprotective effects. Thus, this study aimed to explore the influence of atorvastatin on isoflurane-induced neurodegeneration and underlying mechanisms. Aged C57BL/6 mice (20 months old) were exposed to isoflurane (1.5%) anesthesia for 6 h. Atorvastatin (5, 10, or 20 mg/kg body weight) was administered to the mice for 7 days. Atorvastatin attenuated the isoflurane-induced generation of ROS and apoptosis. Western blotting revealed a decrease in cleaved caspase-9 and caspase-3 expression in line with ROS levels. Furthermore, atorvastatin ameliorated the isoflurane-induced activation of p38MAPK/ATF-2 signaling. In a cellular study, we proved that isoflurane could induce oxidative stress and inflammation by activating the p38MAPK/ATF-2 pathway in BV-2 microglia cells. In addition, SB203580, a selected p38MAPK inhibitor, inhibited the isoflurane-induced inflammation, oxidative stress, and apoptosis. The results implied that p38MAPK/ATF-2 was a potential target for the treatment of postoperative cognitive dysfunction.